PENGARUH CITRA MEREK, KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KARTU PERDANA TELKOMFLEXI (Studi kasus pada konsumen TelkomFlexi di Kecamatan Kota Kudus Kabupaten Kudus) - Nela Evelina; Handoyo Djoko Waloejo; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2013)
Consumer purchasing behavior of a product is influenced by many factors. Each individual has different wish and desires. Product quality is a most factor to the purchasing decision, besides that there are many factors that influence to the purchasing behavior. The purpose at this research is to determine how much the influence of the grand image, product quality, price and promotion of the product TelkomFlexi card to the purchasing decision and also knowing variables that the most dominant influence to the purchasing decision of TelkomFlexi card product at Kudus area. The type of research that used is the type of explanatory research. A sample of 100 respondent was taken that consumers who use TelkomFlexi starter pack. Sampling with purposive techniques. Data analysis techniques using linear regression analysis and SPSS 16.0. Based on the results of the research, it can be concluded that (a) brand image has positive and significant impact on purchasing decision of TelkomFlexi starter pack, (b) there are positive impact and significant on quality variable of product, (c) there are positive impact and significant on price variable, (d) there are positive impact and significant on promotion variable to the purchasing decision of TelkomFlexi starter pack. The most impact variable is promotion variable. Hipotesis test show that there are impact of grand image, product quality, price and promotion to the purchasing decision of TelkomFlexi starter pack. Determination coefisien for variable grand image (X1), product quality (X2), price (X3), and promotion (X4) give 79,2% for purchasing decision at PT. TelkomFlexi and 20,8% influenced by another factors. The suggestion of this research is PT. TelkomFlexi better to increase grand image so that the consumer more knowing the product, low price, keep good quality and defend of product so that the consumers always interest to the products.